Has flood damage being reduced? A resident perspective on the effectiveness of flood management - Lumin Hong; Guangwei Huang (PLoS ONE, 2025)
Flood disasters have been studied intensively and extensively. However, studies to evaluate the long-term effectiveness of flood management from social perspectives are limited. Questions such as whether flood damage has been reduced or exacerbated have been insufficiently examined and poorly answered from the residents’ view angle. Usually, annual flood damage is used to quantify the economic impact of flood. However, as the estimation of flood-caused damage is affected by various uncertainties in methodology, the development of an indicator without ambiguity is needed for the assessment of flood management effectiveness. Moreover, annual flood damage is often the focus of researchers and administrators. The aim of this paper was to address the often-neglected question of what is the right perspective to better understand long-term changes in flood damage over time, and a related question of what perspective is most tangible to residents and can be used to promote public participation in flood risk management. Thus, the present work used Japan’s flood damage data over the past several decades to analyze various flood damage indices and identify the ones that can be used to detect significant changes in flood impacts without uncertainty, which can also bridge science with residents. The main finding is that the number of flooded houses and semi-damaged houses divided by the annual inundated residential area fit for the purpose of the present study. Since house inundation is more tangible to residents than annual flood economic loss, the findings suggested that the resident-oriented indicator can better reflect the change in flood impact and promote residents’ involvement in the building of coping capacity. In addition, the drivers for flood impact reduction in Japan were discussed and a framework for promoting citizen science for flood risk management was proposed. The overall value of the present work is that it has identified and attempted to fill the knowledge gap in flood impact assessment.